Comprehensive High Schools as a Key Approach to Promoting Academic-Vocational Integration in County-Level Secondary Education: Based on Policy Implementation and Educational Reform Perspectives - Yi Silin (Journal of Exploration of Vocational Education, 2025)
Abstract As a new model integrating general and vocational education, comprehensive high schools represent a key pathway for addressing the developmental challenges faced by county-level secondary vocational schools and advancing the integration of academic and vocational education. This paper analyzes the definition and connotation of comprehensive high schools and examines the practical issues confronting county-level vocational schools in terms of resources, social recognition, and curriculum design. It argues for the significance of academic-vocational integration in promoting educational equity, talent cultivation, and social development, and proposes an implementation framework centered on comprehensive high schools. The study finds that through mechanisms such as curriculum integration, student record interoperability, and faculty sharing, comprehensive high schools can effectively break down barriers between academic and vocational tracks, promote balanced regional educational development, and provide high-quality talent support for building a skills-based society.